2011
DOI: 10.1182/blood-2010-12-327346
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis identifies galectin-1 as a predictive biomarker for relapsed/refractory disease in classical Hodgkin lymphoma

Abstract: Considerable effort has been spent identifying prognostic biomarkers in classic Hodgkin lymphoma (cHL). The aim of our study was to search for possible prognostic parameters in advanced-stage cHL using a proteomics-based strategy. A total of 14 cHL pretreatment tissue samples from younger, advanced-stage patients were included. Patients were grouped according to treatment response. Proteins that were differentially expressed between the groups were analyzed using 2D-PAGE and identified by liquid chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 44 publications
(50 reference statements)
4
82
2
1
Order By: Relevance
“…Appropriately, the presence of increased numbers of tissue-infiltrating macrophages is now being examined in prospective clinical trials to see whether this finding can be sufficiently reproducibly demonstrated to justify its use to identify patients for either reduction of treatment because macrophage numbers are very low or escalation of treatment because they are very high. Certain serum markers also seem promising, especially serum TARC, galectin-1, and IL-10, because their prognostic impact has been validated independently [63][64][65]73,76,78,79 and because they can be readily measured not only at diagnosis, when their prognostic importance can be assessed, but also serially during treatment to determine whether they can reliably identify patients whose treatment response is proving to be suboptimal. Finally, examining the overall gene expression profile detectable in biopsy tissue involved with Hodgkin lymphoma, which necessarily profiles the gene expression of the host reactive cells and not the malignant Hodgkin Reed-Sternberg cells, appears capable of separating a minority (29%) of patients with a sixfold worse prognosis from a majority (71%) with a much more favorable prognosis using modern chemotherapy.…”
Section: Risk Factors Reflecting Specific Biologic Characteristicsmentioning
confidence: 99%
“…Appropriately, the presence of increased numbers of tissue-infiltrating macrophages is now being examined in prospective clinical trials to see whether this finding can be sufficiently reproducibly demonstrated to justify its use to identify patients for either reduction of treatment because macrophage numbers are very low or escalation of treatment because they are very high. Certain serum markers also seem promising, especially serum TARC, galectin-1, and IL-10, because their prognostic impact has been validated independently [63][64][65]73,76,78,79 and because they can be readily measured not only at diagnosis, when their prognostic importance can be assessed, but also serially during treatment to determine whether they can reliably identify patients whose treatment response is proving to be suboptimal. Finally, examining the overall gene expression profile detectable in biopsy tissue involved with Hodgkin lymphoma, which necessarily profiles the gene expression of the host reactive cells and not the malignant Hodgkin Reed-Sternberg cells, appears capable of separating a minority (29%) of patients with a sixfold worse prognosis from a majority (71%) with a much more favorable prognosis using modern chemotherapy.…”
Section: Risk Factors Reflecting Specific Biologic Characteristicsmentioning
confidence: 99%
“…1,8 In recent immunohistochemical analyses of primary cHLs, increased Gal1 expression was associated with poorer event-free survival. 9 Given the broadly immunosuppressive activities of Gal1, we reasoned that this soluble lectin might be a potent marker of disease activity and a novel therapeutic target in cHLs. We previously developed a panel of Gal1 monoclonal antibodies (mAbs) and demonstrated the utility of Gal1 as a diagnostic marker of AP-1-dependent lymphoid malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Indeed, in patients with Hodgkin disease, increased Gal-1 expression is correlated with poor prognoses and implicated as a biomarker of disease progression. 14 Although a prior study shows that Gal-1 expression is elevated in epidermotropic malignant T cells in patients with mycosis fungoides, 15 its presence and role in more advanced leukemic forms of CTCL have not been addressed. Here we show that clonal malignant T cells in patients with stage 3 or 4 CTCL exhibited a Th2 cytokine signature and high intracellular Gal-1 expression.…”
mentioning
confidence: 99%